2021
DOI: 10.1021/acs.chemmater.1c00732
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Two-Dimensional Plasmonic Molybdenum Oxide Nanomaterials by Femtosecond Laser Irradiation

Abstract: A novel process to synthesize plasmonic MoO3–X nanosheets is demonstrated, in which MoS2 powders suspended in ethanol/water are irradiated with pulses from a femtosecond laser, resulting in simultaneous Coulomb explosion, photoexfoliation, and oxidation. The oxidation process is found to start with the formation of hydrogen-bonded molybdenum oxide (H X MoO3), followed by the release of −OH2 groups to create oxygen vacancies, and finally, MoO3–X is oxidized to MoO3 after extended irradiation. The formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…[34,46] When the concentration of ethanol is 90%, the MoO 3-X peaks become dominant in the Raman spectrum, consistent with our previous work that 80-90% ethanol is optimum to prepare MoO 3-X from MoS 2 via femtosecond laser irradiation. [34] In the 100% ethanol sample, almost all the Raman peaks belong to MoO 3 . The photo luminescence excitation and emission spectra of the MBs synthesized in 1% and 30% ethanol solvents were also investigated.…”
Section: Role Of Water and Ethanolsupporting
confidence: 89%
See 1 more Smart Citation
“…[34,46] When the concentration of ethanol is 90%, the MoO 3-X peaks become dominant in the Raman spectrum, consistent with our previous work that 80-90% ethanol is optimum to prepare MoO 3-X from MoS 2 via femtosecond laser irradiation. [34] In the 100% ethanol sample, almost all the Raman peaks belong to MoO 3 . The photo luminescence excitation and emission spectra of the MBs synthesized in 1% and 30% ethanol solvents were also investigated.…”
Section: Role Of Water and Ethanolsupporting
confidence: 89%
“…[32,33] Our previous work also successfully synthesized MoO 3-X nanosheets by irradiating MoS 2 suspended in ethanol/water solvents using a femtosecond laser system. [34] When a femtosecond laser pulse interacts with materials, the high electric field of the laser pulse strips electrons from bulk materials, then the bulk materials are dissociated due to mutual repulsion of the photoionized molecular species. The nanoparticles are formed via nucleation and coalescence of the reactive ionized species.…”
Section: Introductionmentioning
confidence: 99%
“…Our calculation results may explain previous experimental results where light absorption and LSPR effects are significantly promoted by the introduction of V O for photo-thermal synergistic catalytic and photothermal therapy. 53–55 As shown in the schematic diagrams in Fig. 7c and d, the perfect-MoO 3 and MoO 3 –H 2 O only absorb UV light through excitations from the VBM to CBM.…”
Section: Resultsmentioning
confidence: 99%
“…[186][187][188] Thanks to the recent development of a diverse range of lasers, laser irradiation as a method to process nanomaterials is blooming. [189][190][191] Different from most conventional material processing techniques, laser irradiation imparts rapid heat and localized high energy to materials, allowing precise control over the material microstructures. 188 Park et al reported the fabrication method of L-shaped graphene nanostructures with a vertical alignment and reduced defect level through laser irradiation.…”
Section: Laser Irradiationmentioning
confidence: 99%